E-Service Quality, Customer Trust and Satisfaction: Market Place Consumer Loyalty Analysis - Muharam, Hari; Chaniago, Harmon; Endraria, Endraria; Harun, Amran Bin (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
Why do online customers become loyal in their purchases on e-commerce sites? We examine how e-service quality, trust, and customer satisfaction affect customer loyalty towards purchasing goods and services. The proposed model also investigates the relationships among e-service quality, trust to loyalty, and satisfaction as a mediator that remains underexplored. The sample of this study is 350 millennial respondents as online buyers in Bogor city. PLS-SEM modeling procedure was used to test the proposed research model. We find that the quality of e-service and trust has a significant favorable influence on customer loyalty, and this effect is mediated by customer satisfaction. This study highlights the role of e-commerce producers in gaining loyalty through efficient service offerings and shape positive psychological in online marketing practices.